Synthesis of Rare Earth Based Pyrochlore Structured (A2B2O7) Materials for Thermal Barrier Coatings (TBCs) - A Review - Sankar , J.; Kumar*, Suresh (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2021)
High temperature application requires protection coatings to ensure the optimal operating cycles to avoid the uncertainty caused by hot gases, foreign contaminates, ambient conditions and other occurrences. In general, protective coating materials can be ceramics, thermally grown oxides, silicates and some rare earth ores. For high-end applications such as gas turbines used in aviation, gas turbines surface are coated with a Thermal Barrier Coating to isolate the components thermally and protect the surfaces. Over the past four decades, those coatings have been employed with the inclusion of Yttrium Stabilised Zirconia (YSZ). The up growing developments on those areas require the coating, which can withstand temperatures above 1200°C. Due to this concern, the alternative to the YSZ based coatings finding has been accelerated. Rare earth oxides with pyrochlore structure ceramics are key interest to provide the coating properties comparatively more than YSZ-based coatings. In this paper, the preparation methods for pyrochlore structured ceramics are discussed. A solid state reaction method widely used for preparing the pyrochlore structure ceramics, but it requires higher temperature and long duration. Wet chemical methods such as precipitation, combustion and hydrothermal techniques produce the pyrochlores at lower temperature comparatively than that of solid state reaction-based methods. In coprecipitation method, intermediate hydrates are reduced into pyrochlores by calcinating at higher elevated temperature. Due to the heat treatment at higher temperature, agglomeration occurs. In the combustion synthesis, fuel-induced exothermic chemical reaction results in porous-structured powders. Upon heat treatment, it results in the porous pyrochlore- structured materials with the agglomeration of particles. Hydrothermal synthesis shows high energy efficiency, maximum yield, uniform particle size and morphology. It was understood that microwave-assisted hydrothermal synthesis requires shorter reaction time. Keywords: thermal barrier coating; solid state reaction; hydrothermal synthesis *Corresponding author: Tel.: (+91) 9894665963 E-mail: sureshme48@gmail.com